Effects of dietary exposure to the engineered nanomaterials CeO2, SiO2, Ag, and TiO2 on the murine gut microbiome. Issue 7 (9th August 2021) - Bredeck, Gerrit; Kämpfer, Angela A. M.; Sofranko, Adriana; Wahle, Tina; Lison, Dominique; Ambroise, Jérôme; Stahlmecke, Burkhard; Albrecht, Catrin; Schins, Roel P. F.
Abstract: Rodent studies on the effects of engineered nanomaterials (ENM) on the gut microbiome have revealed contradictory results. Our aim was to assess the effects of four well-investigated model ENM using a realistic exposure scenario. Two independent ad libitum feeding studies were performed. In study 1, female mice from the local breeding facility received feed pellets containing 1% CeO2 or 1% SiO2 for three weeks. In study 2, both female and male mice were purchased and exposed to 0.2% Ag-PVP or 1% TiO2 for four weeks. A next generation 16S rDNA sequencing-based approach was applied to assess impacts on the gut microbiome. None of the ENM had an effect on the α- or β-diversity. A decreased relative abundance of the phylum Actinobacteria was observed in SiO2 exposed mice. In female mice, the relative abundance of the genus Roseburia was increased with Ag exposure. Furthermore, in study 2, a sex-related difference in the β-diversity was observed. A difference in the β-diversity was also shown between the female control mice of the two studies. We did not find major effects on the gut microbiome. This contrast to other studies may be due to variations in the study design. Our investigation underlined the important role of the sex of test animals and their microbiome composition prior to ENM exposure initiation. Hence, standardization of microbiome studies is strongly required to increase comparability. The ENM-specific effects on Actinobacteria and Roseburia, two taxa pivotal for the human gut homeostasis, warrant further research on their relevance for health.